FATWA MUI TENTANG KEHALALAN VAKSIN COVID-19 DAN KONTRIBUSINYA TERHADAP SOSIALISASI VAKSINASI DI KOTA MEDAN - Syafruddin Syam; Bagus Ramadi; Titi Susanti (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2022)
Abstract: One of the Government's strategic policies in suppressing and stopping the transmission of COVID-19 is to take the vaccination movement seriously. Even though the vaccination program has positive goals, while people are hesitant and even refuse to use vaccines because they are considered illegal and dangerous. Responding to this friction, this is where the importance of the MUI fatwa in socializing that vaccination is very urgent and permissible to do. There are no serious objections to vaccination in Medan City; even the majority of Medan Muslims claim that the MUI fatwa is beneficial. This article includes field research with a qualitative approach. The methodology used is an interpretive study of legal sociology by conducting interviews and reviewing documents related to the MUI fatwa regarding the COVID-19 vaccination. The results conclude that; the Medan City MUI fatwa has been well received by the public and deemed necessary. Second, the effectiveness of the Sinovac halal vaccine has been tested and is of good quality and is allowed to be used. There are no serious objections to vaccination in Medan City; even the majority of Medan Muslims claim that the MUI fatwa is beneficial